The Use of Artificial Intelligence (AI) Technology and Visual Design of Campaign Billboards on The Decision to Vote For Presidential Candidates in Generation Z - Samatan, Nuriyati; Londol, Marwan; Nurhasanah; Robingah; Abdurrahman, Muzakky (International Journal of Advanced Multidisciplinary, 2025)
This research aims to determine the effect of the use of Artificial Intelligence (AI) technology and the visual design of campaign billboards on the decision to vote for presidential candidates in Generation Z. In addition, this research seeks to understand how these two elements interact and influence each other on the choice of Presidential candidates in Generation Z.  This research focuses on how the use of Artificial Intelligence (AI) technology and visual design of billboards in political campaigns to encourage the level of decision to vote for presidential candidates in Generation Z. The research was conducted using quantitative methods and the data collection process was carried out by distributing questionnaires. The sampling technique used in determining the research sample is Probability Sampling, with the Simple Random Sampling technique, the determination of respondents is based on the Slovin Formula with a margin of error level of 0.5% with a sample number of 400 respondents. Data processing in this research was carried out by multiple linear regression analysis using the SPSS (Statistical Product and Service Solutions) version 29 statistical program. The results showed that each of the X variables had a positive and significant influence on the Choice Decision variable (Y).